VALUES TO BE DEVELOPED AMONG SCHOOL CHILDREN - Dr.T.Sireesha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Values are the salient features of the individuals’ behavior in the society. There are different types of individuals having basic individual difference in personality, make-up attitudes, liking, behaviors, views, values, beliefs etc. Value is a type of norm found in various cultures along with other patterns of behavior, values are the more enduring cluster of wants that a given individual strives for thought. The term value is very difficult to define satisfactorily some philosophers even considered it as a fundamental category, which cannot be defined so easily yet the concept of value is so deeply embedded in human actions and thoughts that one should make an effort at least to understand its meaning and reunifications. Only a limited number of investigations had been conducted using measured values as one of the variables. Most of these studies were confined to other countries. It was felt that an investigation of developing values as it is related to measured values would throw more light and provide insight into the dynamics of measured values. against this book ground an attempt was made to related develop values to children side by side it was also aimed to investigate whether there would be any significant difference in the value patterns of boys and girls at the higher and lower classes.